Comprehensive Analysis of Differentially Expressed lncRNAs in Gastric Cancer - Xiao, Nan; Hu, Yang; Juan, Liran (Frontiers in Cell and Developmental Biology, 2020)
Gastric cancer (GS) is the fourth most common malignant tumor. The mechanism underlying GS occurrence and development remains unclear. Previous studies have indicated that long noncoding RNAs (lncRNAs) are significantly associated with gastric cancer, but a systematic understanding of the role of lncRNAs in gastric cancer is lacking. In recent years, with the development of next-generation sequencing technology, tens of thousands of lncRNAs have been discovered. However, a large number of unannotated lncRNAs remain unidentified in different tissues, including potential gastric cancer-related lncRNAs. In this study, RNA-seq data from 16 samples of 8 gastric cancer patients were obtained and analyzed. A total of 1,854 previously unannotated lncRNAs were identified by ab initio assembly, and 520 differentially expressed lncRNAs were validated in the TCGA expression data set. Methylation and CNV array data from the same sample were integrated in the analysis. Changes in DNA methylation levels and copy number variations (CNVs) may be responsible for the differential expression of 91 lncRNAs. Differentially expressed lncRNAs were enriched in coexpressed clusters of genes related to functions such as cell signaling, cell cycle, immune response, metabolic processes, angiogenesis, and regulation of retinoic acid receptors. Finally, a differentially expressed lncRNA, AC004510.3, was identified as a potential biomarker for the prediction of the overall survival of gastric cancer patients.